Plasma concentration of voriconazole under concomitant use of nirmatrelvir/ritonavir in patients with COVID-19: a multicenter retrospective study - Shi, Hao; Zhang, Xuan; Kong, Qihui; Yu, Lingyan; Yu, Zhenwei (Frontiers in Pharmacology, 2025)
BackgroundThe concomitant use of nirmatrelvir/ritonavir and voriconazole is generally contraindicated in clinical practice because of drug‒drug interactions (DDIs). However, emerging clinical data suggest that this DDI is complicated and that the concomitant use of these two drugs may be feasible.MethodsThis was a multicenter retrospective study. Hospitalized patients who were diagnosed with COVID-19 in 2023 and who received concomitant nirmatrelvir-ritonavir and voriconazole were retrospectively included according to preset criteria. Personal information, medication records and voriconazole plasma levels were obtained from the hospital information system. The voriconazole concentrations were analyzed.ResultsA total of 13 hospitalized patients with COVID-19 and 16 voriconazole trough concentrations were included from 4 centers. Half of the patients (8 patients, 50.0%) had voriconazole plasma concentrations within the therapeutic range. The remaining 8 cases (50.0%) fell outside the therapeutic range, including 1 case (12.5%) with subtherapeutic levels and 7 cases (87.5%) with supratherapeutic concentrations.ConclusionThe concomitant use of nirmatrelvir/ritonavir and voriconazole might be feasible, but the dosing of voriconazole needs further study.